Економічна кон’юнктура і тенденції розвитку ринку продовольства - Новальська, Надія Іванівна (My University, 2018)
Розглянуто питання стану внутрішньому ринку продовольчих товарів в Україні. Визначено його взаємозв’язок із питанням забезпечення продовольчої безпеки. Проаналізовано кількісні і якісні характеристики пропорцій попиту і пропозиції продовольчих товарів на внутрішньому ринку України. The issue of the state of the domestic food market in Ukraine is considered. Its relationship with the issue of ensuring food security is determined. The quantitative and qualitative characteristics of the proportions of demand and supply of food products on the domestic market of Ukraine are analyzed.
Keywords: економічна кон’юнктура; economic situation; продовольча безпека; food security; ринок товарів; goods market